news - Tkacheva, Marina; Smirnova, Olga; Gutsol, Olga; Dudnev, Alexander; Grigorieva, Anna (project baikal, 2012)
UIA NewsA Thinking Head and a Nursing CowThe Regular General Meeting of the Members of the Self-Regulatory Organization IndependentPartnership “The Baikal Association of Architects and Engineers” of March 23“BukhArt”: the Beginning of the Second Five-Year PeriodThe VIIth Forum of Architects-Skiers from Siberia and UralThe Second Landscape Conference in Krasnoyarsk“Geo-Decor”, so Simple and Unexpected254 Years and the 20th AnniversaryThe Book “Irkutsk Architects” Arkhangelsk Museum of Wooden Architecture «Malye Korely»The Valletta Principles for the Safeguarding and Management of Historic Cities, Towns and Urban AreasCreative Project in VologdaThe Nomad 2. Circles and Spirals